Dynamically driven inflow onto the galactic center and its effect upon molecular clouds - Hatchfield, H. Perry; Sormani, Mattia C.; Treß, Robin G.; Battersby, Cara; Smith, Rowan J.; Glover, Simon; Klessen, Ralf S. (The astrophysical journal, 2021)
The Galactic bar plays a critical role in the evolution of the Milky Way’s Central Molecular Zone (CMZ), driving gas toward the Galactic Center via gas flows known as dust lanes. To explore the interaction between the CMZ and the dust lanes, we run hydrodynamic simulations in arepo, modeling the potential of the Milky Way’s bar in the absence of gas self-gravity and star formation physics, and we study the flows of mass using Monte Carlo tracer particles. ...
Online veröffentlicht am 23. November 2021
Gesehen am 09.01.2024